Formation mechanism and risk assessment of debris flow geological disasters in Lihong Road, Litong District, Wuzhong City, Ningxia - Wang, Hui; Wang, Guorui; Hu, Zhiyong; He, Xiaofeng; Gong, Yongfeng; Zhang, Gang; He, Zheng; Yan, Jinkai; Zhang, Yaoyao (Frontiers in Earth Science, 2025)
The Lihong Road area in Litong District, Wuzhong City, Ningxia, is highly prone to debris flow disasters due to its steep topography, loose surface materials, and frequent extreme rainfall. This study investigates the formation mechanisms and hazard dynamics of debris flows in this area, with particular attention to both natural factors and anthropogenic influences, such as sand mining. A key innovation of this research lies in integrating terrain modification effects into FLO-2D numerical simulations under varying rainfall scenarios. The results reveal that intense precipitation, steep slopes, and abundant loose materials primarily contribute to debris flow initiation. Simulations show that human-induced topographic changes significantly alter flow patterns and exacerbate risk. The study identifies a critical rainfall threshold of 130.86 mm and a 1-h triggering intensity of 50.86 mm. Hazard zoning based on flow velocity, deposition depth, and inundation range highlights the region’s vulnerability, especially around infrastructure and farmland. This work provides a scientific basis for early warning, engineering mitigation, and regional disaster prevention strategies.